The Implication of Self-Relevant Value and Value of Travelling Consumption on Propensity to Share Electronic Word of Mouth of Traveler - Anggarawati, Sularsih; Saputra, Fachri Eka (International Journal of Social Science and Business, 2021)
This study aims to examine the effect of 3 dimensions of self-relevant value (Reflected Appraisal of Self, Conspicuous Value, and Self-Image Congruity) and 3 dimensions of value of traveling consumption (Desire for Experience Travel, Need for Uniqueness, and Social Esteem) on the tendency for someone to share their experiences on social media (e-WOM). To answer the research objectives, this study uses a quantitative research design using cross sectional time dimension of the study. The questionnaire was used as a sample data collection tool, in which the sampling was done purposively. The data collection method used in this study is by distributing online questionnaires by inserting questionnaires into Google Form, then online questionnaires are distributed through social media such as Facebook, Instagram, and WhatsApp. Appropriate respondents to fill out this questionnaire are people who have visited popular tours in Indonesia, especially young tourists. Data analysis method is planned using Multiple Regression Analysis. The results show that four of the six hypotheses are proven in this study. There are two hypotheses that are rejected, specifically the relationship between conspicuous value on propensity to share e-WOM, and the relationship between self-esteem on propensity to share e-WOM. This study gives a contribution to the body of knowledge on the relationship between self-relevant value and desire to experience travel concepts on propensity of travellers to share their experience on the electronic Word of Mouth (e-WOM).